The performance and diversification potential of non-listed value-add real estate funds in Japan - Martin Hoesli; Graeme Newell; Jufri Marzuki; Rose Neng Lai (Journal of Risk and Financial Management, 2022)
In the aftermath of the COVID-19 pandemic, non-core investments are gaining traction amongst institutional investors due to the shifting preference towards investment vehicles that position higher on the risk-return curve. Non-listed value-add real estate funds in Japan are one such vehicle. This research develops a comprehensive bespoke benchmark total return index using the ANREV database to reflect the performance of Japan-focussed non-listed value-add real estate funds. We compare the performance of such funds with that of other asset classes and perform portfolio and regression analyses. We conclude that there are several advantages to investing in those funds, including: (1) strong absolute total return performance, (2) competitive risk-adjusted performance, and (3) significant portfolio diversification potential in a mixed-asset portfolio context. The strategic implications for real estate investors are also assessed.
Keywords: 650; Japan; non-listed real estate fund; real estate investment strategy; risk-adjusted performance; value-add real estate fund